3-Thio-5-(N-aryl-N′-arylguanyl)-1,2,4-dithiazoles as potential anti-convulsant and analgesic agents - Srivastava K.; Pandeya S. (My University, 2025)
The synthesis and biological activities of a number of substituted 3-thio-5-(N-aryl-N′-arylguanyl)-1,2,4-dithiazoles are reported. The aromatic substitutents m-CH3 3, p-CH3 4 and p-bromo 11 produced compounds with potent anti-convulsant properties in rats and compared favorably with the standard anti-convulsant drugs phenytoin and phenobarbitone-sodium in a number of test situations. In the analgesic test, most of the compounds exhibited analgesic activity with particular reference to p-CH3 4 substitution being most potent in the series. © 1993.